Potency and stability of liposomal Amphotericin B formulated for topical management of Aspergillus spp. infections in burn patients. Issue 3 (July 2020) - Laurent, Alexis; Pantet, Olivier; Laurent, Lydie; Hirt-Burri, Nathalie; de Buys Roessingh, Anthony; Raffoul, Wassim; Laurent, Philippe; Monod, Michel; Applegate, Lee Ann
Highlights: Fungal infections are important mortality factors in severely burned patients. Amphotericin B is a drug of choice for infections in burn victims. Experimental liposomal Amphotericin B is relatively easy and inexpensive to obtain. Liposomes allow for consistent activity of Amphotericin B over time. Customized liposomal Amphotericin B is highly interesting for severe burn patient antimicrobial care. Abstract: Background: Systemic fungal infections are an important mortality factor when considering severely burned patients. Preventive topical pharmacotherapeutic management of deep fungal infections remains of secondary concern when initially treating a burn victim, despite high inherent lethal risks. Indeed, the possible subsequent invasions of newly accessible deep tissues and bone by opportunistic fungi often prove fatal. Amphotericin B is a broad-spectrum antifungal agent of choice for infections in burn victims. Intravenous administration is limited by drug-related nephrotoxicity. Novel topical Amphotericin B preparations to be applied in burn centers would therefore limit the systemic adverse effects of the active principle while preventing dissemination of sensitive pathogens and thus help reducing infectious and drug-related mortality. Objective: To establish the need for new topical pharmacotherapeutic management options to treat burn wound fungal infections and conceptually determine the applicability of liposomal Amphotericin B for such cases. Methods: Experimental liposomal Amphotericin B was prepared with commercial components and tested in vitro in our mycology laboratory to determine efficacy, stability and potential for topical application on our burn patients. Results: Data showed equivalent or superior in vitro activity of liposomal Amphotericin B versus unbound drug against Aspergillus fumigatus and superior physical and pharmacologic effect stability over time. Conclusion: Topical and relatively inexpensive liposomal Amphotericin B as described in this work is an interesting, potentially mortality-reducing candidate regarding fungal infections in early and severe burn wound management.